Analysis of Social-Emotional Skills on Vocational High School Students - Windy Widiyastuti; Senowarsito Senowarsito; Indri Kustantinah; Sumarjo Sumarjo (Universitas Pahlawan Tuanku Tambusai, 2023)
The importance of mastering social and emotional skills is said to be at the core of future student success. Emotional changes are closely related to social phenomena, and this is included in the context of learning in the classroom, in the school environment, and outside the school ecosystem. Learning that interprets social-emotional competence is called social and emotional learning (SEL). The impact effectiveness of social-emotional learning is said to help students to adulthood from aspects of student welfare such as education, employment, and social income. However, in the context of the national curriculum, few studies are related to social-emotional learning, especially for students in vocational high schools (SMK). This study aims to analyse the social-emotional abilities of vocational high school students. Socio-emotional development is essential for children to adapt to changes in the learning system. Good socio-emotional development can make it easier for children to get along and learn better, such as in various activities in a social environment. Socio-emotional development plays an essential role in encouraging children's progress. The research method used is qualitative with a descriptive approach. Data was collected by making an interview guide in a Google Form. The research subjects were 36 students of class X PM 1. The study shows that vocational high school students have good social-emotional abilities. As much as 80.1% have good self-awareness, 91.7% have good self-management, 83.3% have good social awareness skills, 97.2% have mature relationship skills abilities, and 83.3% have good responsible decision-making abilities too. Keywords: Social-Emotional; Students; Vocational High School.